2019
DOI: 10.20944/preprints201903.0164.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Review on Smart Electro-Clothing Systems (SeCSs)

Abstract: This paper presents an overview of the smart electro-clothing systems (SeCSs) targeted at health monitoring, sports benefits, fitness tracking, and social activities. Technical features of the available SeCSs, covering both textile and electronic components, are thoroughly discussed and their applications in the industry and research purposes have been highlighted. In addition, it also presents the developments in the associated areas of wearable sensor systems and textile-based dry sensors. As it became evide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A, illustration of how rigid control modules are used in e‐textiles. Reproduced with permission 4 . Copyright 2020, the authors, published by MDPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A, illustration of how rigid control modules are used in e‐textiles. Reproduced with permission 4 . Copyright 2020, the authors, published by MDPI.…”
Section: Discussionmentioning
confidence: 99%
“…Before discussing e‐textile joining technologies, it is useful to briefly review e‐textile applications and different methods to construct e‐textiles, to understand the criteria that must be met by such joining technologies. A 2020 review of “smart electro‐clothing systems” shows that the two leading categories of commercially available e‐textiles are sports and healthcare 4 . Embedding sensors in garments can enable data collection on sports performance, for example tracking heart rate 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, everyone has seen the advertisements for glucose sensors that ensure appropriate insulin supply [2,13] . Sensors can be fabricated on paper or etextiles for wireless powered disposable sensing devices [14,15] . Devices have recently been brought to market for niche problems in diagnostics.…”
Section: Data Acquisition In Diagnostics and Rehabilitationmentioning
confidence: 99%
“…Thirdly, smart socks cannot be washed; for washing, first the electronic components must be removed. This latter disadvantage is under research to be alleviated by designing for the textiles a waterproof enclosure in which the electronic components might be introduced [ 21 , 22 ].…”
Section: Smart Sock Definition and Principles Of The Technologymentioning
confidence: 99%
“…The same SP is automatically calculated by the Zebris system (ZSP), and it was used as the gold standard value. Based on the results of the comparison made between the two systems ( Table 5 ), the authors concluded that Sensoria smart socks are a reliable alternative to Zebris and, moreover, benefit from a lower cost [ 21 , 30 ].…”
Section: Description Of Proposed Solutions Using Smart Socks For Gmentioning
confidence: 99%